Transmembrane START domain proteins: in silico identification, characterization and expression analysis under stress conditions in chickpea (Cicer arietinum L.). (1st February 2016) - Satheesh, Viswanathan; Chidambaranathan, Parameswaran; Jagannadham, Prasanth Tejkumar; Kumar, Vajinder; Jain, Pradeep K.; Chinnusamy, Viswanathan; Bhat, Shripad R.; Srinivasan, R.
Abstract : Steroidogenic acute regulatory related transfer (StART) proteins that are involved in transport of lipid molecules, play a myriad of functions in insects, mammals and plants. These proteins consist of a modular START domain of approximately 200 amino acids which binds and transfers the lipids. In the present study we have performed a genome-wide search for all START domain proteins in chickpea. The search identified 36 chickpea genes belonging to the START domain family. Through a phylogenetic tree reconstructed with Arabidopsis, rice, chickpea, and soybean START proteins, we were able to identify four transmembrane START (TM-START) proteins in chickpea. These four proteins are homologous to the highly conserved mammalian phosphatidylcholine transfer proteins. Multiple sequence alignment of all the transmembrane containing START proteins from Arabidopsis, rice, chickpea, and soybean revealed that the amino acid residues to which phosphatidylcholine binds in mammals, is also conserved in all these plant species, implying an important functional role and a very similar mode of action of all these proteins across dicots and monocots. This study characterizes a few of the not so well studied transmembrane START superfamily genes that may be involved in stress signaling. Expression analysis in various tissues showed that these genes are predominantly expressed in flowers and roots of chickpea. Three of the chickpea TM-START genes showed induced expression in response to drought, salt, wound and heat stress, suggesting their role in stress response.